A lower value for quantitative ultrasound at radius is an additional indicator of metabolic syndrome and cardiovascular disease risk. (1st April 2013) - Tao, Bei; Li, Zhen; Zhao, Hong‐Yan; Sun, Li‐Hao; Zhao, Lin; Li, Xiao‐Ying; Wang, Wei‐Qing; Ning, Guang; Liu, Jian‐Min
Summary Background The relationships between quantitative ultrasound (QUS) values, metabolic syndrome (MetS) and cardiovascular disease (CVD) risk are unclear. Objective The objective was to determine the relationships between QUS and MetS as well as CVD risk. Design This was a cross‐sectional study conducted in Shanghai, China. Patients One‐thousand four hundred and thirty‐nine Chinese women and men with or without MetS were studied. Measurements Speed of sound (SOS) at radius, phalanx and tibia and their relationships with MetS and Framingham's 10‐year cardiovascular disease risk scores were investigated. Results Premenopausal women with MetS had significant lower SOS at radius than those without MetS after adjusting for age, BMI and fat mass percentage (P = 0·02). The radius SOS was negatively associated with waist circumference (r = −0·109, P = 0·025), waist‐to‐hip ratio (r = −0·124, P = 0·01) and 2 h postprandial glucose level (r = −0·125, P = 0·012) in premenopausal women. Waist circumference, waist‐to‐hip ratio and 2 h postprandial glucose level increased with the decreasing tertiles of radius SOS after adjustment of age (P = 0·003, 0·002 and 0·008, respectively). The CVD risk increased with decreasing tertiles of radius SOS in postmenopausal women even after the adjustment of age, years since menopause, MetS components, smoking and alcohol habits (P < 0·001), but not in premenopausal women and men. Conclusions Lower radius SOS is associated with greater risks of MetS and CVD in premenopausal and postmenopausal women, respectively. The QUS value derived from non‐weight‐bearing site, such as radius, may represent an additional indicator of MetS and CVD risk in women.